2014
DOI: 10.1080/02827581.2014.960892
|View full text |Cite
|
Sign up to set email alerts
|

Genetic stability analysis of introducedBetula pendula, Betula kirghisorum, andBetula pubescensfamilies in saline-alkali soil of northeastern China

Abstract: Approximately, 20% of arable land worldwide, as well as nearly half of irrigated land, is subjected to salt stress. Osmotic stress and ion toxicity due to saline soils cause low crop yields. In this study, we introduced 18 families of salt-tolerant birch (Betula pendula Roth., Betula kirghisorum Sav.-Ryczg., and Betula pubescens Ehrh) into five high-salinity locations in northeastern China and evaluated their survival abilities. We also analyzed variation and stability of genotypeenvironment interactions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…et Zucc. and Pinus taeda L. [14][15][16], in branchiness, straightness and wood density for Eucalyptus regnans F. Muell., Pinus radiate D. Don and Eucalyptus grandis W. Hill ex Maiden [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…et Zucc. and Pinus taeda L. [14][15][16], in branchiness, straightness and wood density for Eucalyptus regnans F. Muell., Pinus radiate D. Don and Eucalyptus grandis W. Hill ex Maiden [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…; Rae et al 2008), white spruce (Picea glauca (Moench) Voss; Rweyongeza 2011), birch (Betula spp. ; Zhao et al 2014) and lodgepole pine (Pinus contorta Douglas; Wu and Ying 2001).…”
Section: Biplot Analysesmentioning
confidence: 99%
“…Several plants are sensitive to abiotic stress, withered, and then died. Despite B. platyphylla is an abiotic stress tolerance tree species, EL value was found to be increased by abiotic stress (Zhao et al 2014;Beloiu et al 2020). Using Evans Blue Staining and the EL rate assay, it was shown that drought stress damaged the B. platyphylla cell membrane (Wen et al 2019).…”
Section: Electrolyte Leakagementioning
confidence: 99%